DETERMINATION OF ATTRACTION BASED ON THE LAYER OF THE REGION ROAD MR. TEUKU MOH. HASAN - Ziak, Zafirul; Fadhly, Noer; Caisarina, Irin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2021)
The spatial structure of Banda Aceh City with the strategy of developing Banda Aceh RTRW 2009-2029 describes city activities in a schematic manner, namely divided into old city centers and new city centers. The new city center is centered in the Batoh or Lamdom area which administratively will serve Lueng Bata and Baiturrahman sub-districts.The formulation of the problem is how the relationship between land use and trip generation on Teuku Moh. Hasan Street East side Hasan. In order to know the capacity and land use influence which is caused to the road, it is necessary to know the capacity, volume, and factors causing the attraction and generation at the location. The results of data collection and processing obtained from the capacity Teuku Moh. Hasan Street is 2696.1 smp/hour. The generation model obtained in layer 1 of the research location which is a commercial land use is Y = -0.629 + 0.056 X2 + 1.002 X3, for layer 2 the research location which is a residential land use is Y = 0.409 + 1.179 X1 + 0.588 X3 + 0.440 X5 and layer 3 research locations which are residential land use are Y = -1.057 + 1.796 X1 + 0.408 X2.Keywords: trip generation and attraction, land use, regression method